Global Imbalances and External Adjustment after the Crisis - Lane, Philip (IMF Working Papers; Working Paper ;, 2014)
This paper has two objectives. First, it reviews the recent dynamics of global imbalances (both 'flow' and 'stock' imbalances), with a special focus on the shifting position of Latin America in the global distribution. Second, it examines the cross-country variation in external adjustment over 2008-2012. In particular, it shows how pre-crisis external imbalances have strong predictive power for post-crisis macroeconomic outcomes, allowing for variation across different exchange rate regimes. We emphasize that the bulk of external adjustment has taken the form of 'expenditure reduction', with 'expenditure switching' only playing a limited role.